Controlled molecular assemblies of chiral boron dipyrromethene derivatives for circularly polarized luminescence in the red and near-infrared regions. Issue 8 (7th February 2023) - Sakai, Hayato; Suzuki, Yudai; Tsurui, Makoto; Kitagawa, Yuichi; Nakashima, Takuya; Kawai, Tsuyoshi; Kondo, Yuta; Matsuba, Go; Hasegawa, Yasuchika; Hasobe, Taku
Abstract : We demonstrated the aggregation-enhanced emission and circularly polarized luminescence of chiral 1, 1′-bi-2-naphthol-substituted boron dipyrromethene derivatives in the red and near-infrared regions. Abstract : Chiral 1, 1′-bi-2-naphthol (BINOL)-substituted boron dipyrromethene (BODIPY) derivatives with different numbers of phenyl groups at the 2 and 6 positions (denoted as n Ph-B-BODIPY; n = 0, 1, 2) were newly synthesized to examine the aggregation-enhanced emission and circularly polarized luminescence (CPL) in the red and near-infrared (NIR) regions. Upon injection of THF solution of n Ph-B-BODIPY into H2 O, 0Ph-B-BODIPY underwent controlled self-assembly to produce fibrous nanoarchitectures, whereas spherical nanoparticles were formed in 1Ph-B-BODIPY and 2Ph-B-BODIPY. Absorption and CD spectra of 0Ph-B-BODIPY nanofibers demonstrated a red-shifted and split spectrum corresponding to the 0-0 band, suggesting strong interaction between neighbouring 0Ph-B-BODIPY units. Such fibrous assemblies exhibited a broad emission spectrum with multiple bands ranging from the visible to the near-infrared (NIR) region due to the multiple aggregate states. Consequently, 0Ph-B-BODIPY nanofibers demonstrated a broad circularly polarized luminescence (CPL) spectrum in the red to NIR regions together with the enhanced dissymmetry factors ( g lum ) relative to 0Ph-B-BODIPY (monomer) and 1Ph-B-BODIPY nanoparticles.